Analisis Partisipasi Politik Digital oleh Mahasiswa dalam Menyuarakan Aspirasi Kebijakan Publik - Triananingsih; Muksitun, Naila Nurul; Putri, Andira Maretha; Dewi, Intan Kusuma; Al Mansyur, Bagas Huda; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2026)
Digital political participation among students has grown significantly alongside the increasing use of social media as a platform for expressing public aspirations. However, its effectiveness remains contested due to the prevalence of slacktivism and the limited empirical evidence regarding its actual contribution to public policy processes. This study aims to examine the influence of digital political participation on students’ ability to articulate public policy aspirations. A quantitative survey approach was employed involving 72 students from the Public Administration Study Program at Universitas Tidar, selected through simple random sampling. Data were collected using an online questionnaire based on a five-point Likert scale and analyzed through Pearson correlation and simple linear regression. The findings reveal that digital political participation has a positive and significant effect on students’ ability to voice public policy aspirations (r = 0.682; p < 0.01; R² = 0.465). These results indicate that higher levels of engagement in digital political activities are associated with a greater capacity to express and disseminate policy-related aspirations. The findings also support the Uses and Gratifications Theory, suggesting that students utilize social media to fulfill cognitive, personal integrity, and social interaction needs. Nevertheless, slacktivism remains a challenge, as symbolic online actions often fail to translate into meaningful civic engagement. This study contributes to the growing literature on digital democracy in Indonesia and highlights the importance of strengthening critical political literacy and fostering more substantive forms of student participation in digital spaces.